2021
DOI: 10.3390/insects12030220
|View full text |Cite
|
Sign up to set email alerts
|

Organic Farming and Cover-Crop Management Reduce Pest Predation in Austrian Vineyards

Abstract: Habitat simplification and intensive use of pesticides are main drivers of global arthropod declines and are, thus, decreasing natural pest control. Organic farming, complex landscapes, and local vineyard management practices such as implementation of flower-rich cover-crop mixtures may be a promising approach to enhance predator abundance and, therefore, natural pest control. We examined the effect of organic versus integrated management, cover-crop diversity in the vineyard inter-rows, and landscape composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…Our results showed that within the most abundant genera were Coccinella and Chrysoperla, who are predators of aphids, and Sphaerophoria, who perform both pollination and predation functions. These observations coincide with those obtained by other authors [57,59,60,70,71] and prove that cover plants are a great tool for IPM.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that within the most abundant genera were Coccinella and Chrysoperla, who are predators of aphids, and Sphaerophoria, who perform both pollination and predation functions. These observations coincide with those obtained by other authors [57,59,60,70,71] and prove that cover plants are a great tool for IPM.…”
Section: Discussionsupporting
confidence: 92%
“…Predatory and phytophagous beetles were not affected by the farming system. While this result is somewhat surprising, similar trends have been reported in other studies [30,33]; only the month drove the abundances of these trophic gilds. Summer drought is the defining feature of the Mediterranean climate.…”
Section: Discussionsupporting
confidence: 90%
“…Organic farming generally supports greater farmland biodiversity and benefits a range of taxa; however, the extent of those benefits is not completely understood, and generalization is not easy across taxa and functional groups [25,[29][30][31]. Although the benefits of organic farming seem to be less prominent in perennial than in annual crops, organic management of fruit orchards may increase insect diversity, improving the balance between sustainability and productivity in the agroecosystem [26,32,33]. Information on insect responses to farming system is available for perennial crops, such as vineyards, apple orchards, and olive orchards [32,34,35], but limited for cherry orchards, even though they comprise 426,000 ha of land worldwide and produce more than 2 million metric tons of cherries annually [36].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ostandie et al (2021) showed highly variable responses across organisms of multiple trophic levels to organic viticulture. Moreover, several studies indicate that biodiversity may not benefit to the same degree from organic farming in perennial vineyard systems as in annual systems (e.g., bees and pollinators: Brittain, Bommarco, Vighi, Settele, & Potts, 2010; Kehinde & Samways, 2012; grasshoppers: Bruggisser et al, 2010; plants: Bruggisser et al, 2010; predatory mites: Reiff, Kolb, et al, 2021; spiders: Bruggisser et al, 2010; Kolb, Uzman, Leyer, Reineke, & Entling, 2020). Only recently, first information about the effect of organic viticulture on carabid beetles became available (Caprio, Nervo, Isaia, Allegro, & Rolando, 2015; Muneret et al, 2019; Ostandie et al, 2021; Uzman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%